1983
DOI: 10.1159/000287759
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and Vocational Long-Term Outcomes of Cardiac Rehabilitation with Postinfarction Patients under the Age of Forty

Abstract: 70 male postinfarction patients, who were under 40 years of age at the time of transmural myocardial infarction, participated in an inpatient control examination 3.8 years following first hospitalization (mean age: 40 years, SD = 3.5 years). A multivessel disease occurred in 52% of the patients, in 80% a multilocular disease was diagnosed and in 25 % coronary angiography indicated a progression in coronary sclerosis. Coronary risk factors had been considerably reduced. 78% were capable of working. Job-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…One study of men who had suffered an MI before age 40 indicated by coronary angiograms more progression of coronary atherosclerosis over five years in those with low job decision latitude than in others (74). However, another study of men who had suffered an MI before age 45, did not support this hypothesis (88).…”
Section: Atherosclerosismentioning
confidence: 97%
“…One study of men who had suffered an MI before age 40 indicated by coronary angiograms more progression of coronary atherosclerosis over five years in those with low job decision latitude than in others (74). However, another study of men who had suffered an MI before age 45, did not support this hypothesis (88).…”
Section: Atherosclerosismentioning
confidence: 97%